SheppHeartCABG trial—comprehensive early rehabilitation after coronary artery bypass grafting: a protocol for a randomised clinical trial. Issue 1 (17th January 2017) - Højskov, Ida Elisabeth; Moons, Philip; Hansen, Niels Viggo; La Cour, Søren; Olsen, Peter Skov; Gluud, Christian; Winkel, Per; Lindschou, Jane; Thygesen, Lau Caspar; Egerod, Ingrid; Berg, Selina Kikkenborg
Abstract : Introduction: Patients undergoing coronary artery bypass graft surgery often experience a range of symptoms. Studies indicate that non-pharmacological interventions such as exercise training and psychoeducation have a positive physiological and psychological effect in early outpatient rehabilitation. The SheppHeartCABG trial will investigate the effect of early comprehensive rehabilitation in early phase rehabilitation versus usual care. The aim of this paper is to present the protocol for the SheppHeartCABG trial. Methods/analysis: SheppHeartCABG is an investigator-initiated randomised clinical superiority trial with blinded outcome assessment, employing 1:1 central randomisation to rehabilitation plus usual care versus usual care alone. On the basis of a sample size calculation, 326 patients undergoing coronary artery bypass grafting will be included from two clinical sites. All patients receive usual care and patients allocated to the experimental intervention follow 4 weeks rehabilitation consisting of an exercise programme, psycho-educative consultations and a compact mindfulness programme. The primary outcome is physical function measured by the 6-min walk test. The secondary outcomes are mental health and physical activity measured by the Medical Outcome Study Short Form (SF-12), anxiety and depression measured by the Hospital Anxiety and Depression Scale questionnaire, physical, emotional and global scores by the HeartQoL questionnaire, sleep measured by the Pittsburgh Sleep Quality Index, pain measured by the Örebro Musculoskeletal Screening Questionnaire and muscle endurance measured by the sit-to-stand test. A number of explorative analyses will also be conducted. Ethics and dissemination: SheppHeartCABG is approved by the regional ethics committee (no. H-4-2014-109) and the Danish Data Protection Agency (no. 30-1309) and is performed in accordance with good clinical practice and the Declaration of Helsinki in its latest form. Positive, neutral and negative results of the trial will be submitted to international peer-reviewed journals. Furthermore, results will be presented at national and international conferences relevant to the subject fields. Trial registration number: NCT02290262; pre-results.